SARS-CoV-2 coinfections among pertussis cases identified through the Enhanced Pertussis Surveillance system in the United States, January 2020–February 2023 - Berry, Isha; Cole, Matthew; Silk, Benjamin; Havers, Fiona P.; Youngkin, Erin; Misiorski, Adam; Sefton, Samantha; Vang, Yeng; Stanislawski, Emma; McGuire, Suzanne; Silhan, Noel; Skoff, Tami H; et al. (PloS one, 2024)
Bacterial and viral respiratory coinfections are common, but the prevalence of SARS-CoV-2 infections among pertussis cases has not been estimated. We examine the prevalence and temporality of SARS-CoV-2 infections among pertussis patients and describe pertussis clinical severity among patients with and without SARS-CoV-2 coinfections. Confirmed and probable pertussis cases among individuals with cough onset between January 1, 2020 and February 15, 2023 were identified through surveillance in seven Enhanced Pertussis Surveillance (EPS) sites. Pertussis cases with a laboratory-confirmed SARS-CoV-2 infection detected within 30 days before or after pertussis cough onset were defined as coinfections. We describe patient demographics, symptoms, and severe complications and outcomes (seizures, encephalopathy, pneumonia, hospitalization, or death) by coinfection status. Among 765 pertussis cases reported during the study period, the prevalence of SARS-CoV-2 coinfections was 0.78% [6/765]. Among the six patients meeting the coinfection definition, the majority (83.3% [5/6]) had SARS-CoV-2 infections detected following pertussis cough onset. Compared to those with no known coinfection, a higher proportion of those with coinfections reported severe complications or outcomes (50.0% [3/6] vs. 5.2% [36/694]). Although the prevalence of pertussis patients with SARS-CoV-2 coinfections was low, patients with coinfections reported more severe complications and outcomes compared to those with pertussis alone. Given the decline in reported pertussis cases during the COVID-19 pandemic, continued monitoring of pertussis incidence alongside respiratory viral infections will be important as the pertussis burden returns to pre-pandemic levels.